Prophylactic ureteral catheter placement for minimally invasive colorectal surgery. Issue 1 (2nd January 2020) - Dowd, Katherine E.; Muse, Tommy O.; Lowry, Patrick S.; Essani, Rahila
Abstract: Ureteral catheter placement for identification of ureters during colorectal surgery has been a controversial subject with ill-defined indications. We present a case of ureteral catheter placement wherein the patient required readmission for renal failure with intervention under local anesthesia. This case highlights the importance of patient selection for catheter placement and clinical follow-up, as well as the need for prospective studies to determine the risk-benefit ratio of preoperative catheters.